Experimental study on the influence of lapping plate materials on the quality of both sides cylindrical rollers machining - Tianchen Zhao; Jiahong Ruan; Kaiping Feng; Luguang Guo; Hongyu Chen; Binghai Lyu; Junkai Ding; Xiaoliang Jiang (Scientific Reports)
Abstract The both-sides machining method can obtain high precision cylindrical rollers, but there is a drawback that the lapping plate is easy to wear, which restricts further improvement in the quality of rollers machining. Aiming to solve this problem, a both-sides machining method using hard ceramic lapping plate is proposed. Friction and wear experiments with different lapping plate materials, along with the corresponding comparative machining experiments, demonstrated the superior performance of Al2O3 ceramic lapping plate in terms of roundness (0.23 μm), cylindricity (0.58 μm), straightness (0.489 μm), surface roughness (11.3 nm). By studying the influence of performance indicators, the optimal process parameters for cylindrical rollers machining were obtained. The durability of the Al2O3 ceramic lapping plate was also analyzed. The study fully confirm that the hard ceramic significantly enhances lapping plate wear resistance, machining precision and consistency, which provides a new approach to ultra-precision machining of cylindrical rollers.